Economic control of quality of manufactured product - Shewhart, Walter A (American Society for Quality Control, 1980)
"50th anniversary commemorative reissue"--T.p. verso; Reprint. Originally published: New York : Van Nostrand, 1931.; Includes bibliographical references and indexes